Consumer Agency and Sustainability Perceptions: Comments on Home Appliances Advertising on Instagram - Eliza Bachega Casadei (Communication Today, 2025)
This article examines the roles of symbolic, material, and competence agencies as reflected in consumer comments on Electrolux’s sustainability campaigns on Instagram, and how these agencies shape consumer perceptions of the brand’s environmental responsibility. Drawing on the theoretical and methodological foundations of Content Analysis, the study reveals that communications promoting technological innovations that facilitate sustainable practices – without demanding significant changes to consumers’ daily habits – are better received. In contrast, campaigns urging more active changes in daily practices face resistance and generate substantial backlash, including accusations of greenwashing. This study underscores the importance of balancing technological innovation with culturally sensitive communication strategies that resonate with consumers’ socio-cultural contexts and personal agency.